Double UP: A Dual Color, Internally Controlled Platform for in utero Knockdown or Overexpression - Taylor, Russell J.; Carrington, Justin; Gerlach, Leah R.; Taylor, Kendra L.; Richters, Karl E.; Dent, Erik W. (Frontiers in Molecular Neuroscience, 2020)
In utero electroporation is a powerful tool for testing the role of genes in neuronal migration and function, but this technique suffers from high degrees of variability. Such variability can result from inconsistent surgery, developmental gradients along both rostral-caudal and medial-lateral axes, differences within littermates and from one litter to another. Comparisons between control and experimental electroporations rely on section matching, which is inherently subjective. These sources of variability are cumulative, leading to difficult to interpret data and an increased risk of both false positives and false negatives. To address these limitations, we developed two tools: (1) plasmids, termed Double UP and Double DOWN, which combine LoxP-flanked reporters and limiting Cre dosages to generate internal controls and (2) an automated program for unbiased and precise quantification of migration. In concert, these tools allow for more rigorous and objective experiments, while decreasing the mice, time and reagents required to complete studies.